Additional High Input Low Output Impedance Analog Networks. (26th September 2013) - Maheshwari, Sudhanshu; Chaturvedi, Bhartendu
Abstract : This paper presents some additional high input low output impedance analog networks realized using a recently introduced single Dual-X Current Conveyor with buffered output. The new circuits encompass several all-pass sections of first- and second-order. The voltage-mode proposals benefit from high input impedance and low output impedance. Nonideality and sensitivity analysis is also performed. The circuit performances are depicted through PSPICE simulations, which show good agreement with theory.